Da’wah Based Sosial Entrepreneurship a Field Study on the Tidore Muslim Community - Abdurrahman Hi. Usman; Bahtiar Bahtiar; Isbat Isbat; Bayanudin Sudin; Rifal Salasa; Muhammad Yunus (Electronic Journal of Education, Social Economics and Technology, 2025)
This research aims to analyze the practice of da'wah-based social entrepreneurship in the Muslim community of Tidore, including its forms of implementation, the integration of da'wah with economic activities, and its impact on the economic empowerment of the community. This research uses a qualitative approach with a field study method thru observation, in-depth interviews, and documentation of religious figures, business owners, and community members. The research results show that social entrepreneurship based on da'wah in Tidore is realized thru community-based micro-enterprises managed collectively by the congregation, such as halal food businesses and basic necessities kiosks. Da'wah integration is carried out thru the model of exemplary da'wah (da'wah bil-hal), where the values of honesty, trustworthiness, and justice are directly implemented in business practices. The impact is evident in increased economic independence, strengthened social solidarity, and the growth of Islamic economic ethics within the community. This research confirms that social entrepreneurship based on da'wah has the potential to become a contextual and sustainable model for empowering the community's economy.